Temporal Lobe Epilepsy Perturbs the Brain‐Wide Excitation‐Inhibition Balance: Associations with Microcircuit Organization, Clinical Parameters, and Cognitive Dysfunction - Ke Xie; Jessica Royer; Raul Rodriguez‐Cruces; Linda Horwood; Alexander Ngo; Thaera Arafat; Hans Auer; Ella Sahlas; Judy Chen; Yigu Zhou; Sofie L. Valk; Seok‐Jun Hong; et al. (Advanced Science)
Abstract Excitation‐inhibition (E/I) imbalance is theorized as a key mechanism in the pathophysiology of epilepsy, with ample research focusing on elucidating its cellular manifestations. However, few studies investigate E/I imbalance at the macroscale, whole‐brain level, and its microcircuit‐level mechanisms and clinical significance remain incompletely understood. Here, the Hurst exponent, an index of the E/I ratio, is computed from resting‐state fMRI time series, and microcircuit parameters are simulated using biophysical models. A broad decrease in the Hurst exponent is observed in pharmaco‐resistant temporal lobe epilepsy (TLE), suggesting more excitable network dynamics. Connectome decoders point to temporolimbic and frontocentral cortices as plausible network epicenters of E/I imbalance. Furthermore, computational simulations reveal that enhancing cortical excitability in TLE reflects atypical increases in recurrent connection strength of local neuronal ensembles. Mixed cross‐sectional and longitudinal analyses show stronger E/I ratio elevation in patients with longer disease duration, more frequent electroclinical seizures as well as interictal epileptic spikes, and worse cognitive functioning. Hurst exponent‐informed classifiers discriminate patients from healthy controls with high accuracy (72.4% [57.5%–82.5%]). Replicated in an independent dataset, this work provides in vivo evidence of a macroscale shift in E/I balance in TLE patients and points to progressive functional imbalances that relate to cognitive decline.